Insights into the structure of the diiron site of RIC from Escherichia coli. Issue 4 (9th January 2015) - Nobre, Lígia S.; Lousa, Diana; Pacheco, Isabel; Soares, Cláudio M.; Teixeira, Miguel; Saraiva, Lígia M.
Abstract : Repair of Iron Centres (RICs) are a widely‐spread family of diiron proteins involved in the protection of iron–sulphur‐containing enzymes from nitrosative and oxidative stress. Here, homology‐based modelling was used to predict putative ligands of the RIC diiron centre in E. coli . Site‐directed mutagenesis studies showed that several conserved residues modulate the spectroscopic properties of the diiron centre, and mutations in H129, E133 and E208 abrogated RIC ability to protect aconitase. Taken together, these data led to a structural model of a diiron centre inserted in a four‐helix bundle fold and coordinated by H84, H129, H160, H204, E133 and E208. Moreover, two μ‐carboxylate bridges involving E133 and E208 were found to be required for assembly of a stable diiron centre. Abstract : Structural model of the E. coli RIC diiron centre is presented. Conserved residues H84, H129, H160, H204, E133 and E208 are ligands of the diiron centre. Residues E133 and E208 form two μ‐carboxylate bridges essential for RIC assembly.